Ergodic sum‐rate analysis for multicast network with wireless energy harvesting relay. Issue 10 (20th June 2019) - Liu, Yingting; Ding, Haiyang; Pan, Zhengwei; Yan, Chunman; Yang, Hongwu
Abstract : In the letter, a wireless energy harvesting (WEH) multicast network is proposed. Two source nodes communicate with their respective destination nodes via a WEH relay node. Adopting the power splitting relaying (PSR) protocol and analogue network coding (ANC), the relay node simultaneously harvests the energy and receives the information from the signals transmitted by the two source nodes in the first time slot ( T / 2 ), and retransmits the amplified signal to the destination nodes in the second time slot ( T / 2 ) using all harvested energy. The analytical expressions of the ergodic sum‐rate of the proposed network are derived. Numerical results corroborate the derived expressions and show that the proposed scheme nearly doubles the maximal ergodic sum‐rate in comparison with the conventional unicast four time slots WEH scheme.